Taking a Systematic Approach to Resident Wellness: A Pilot Study. (April 2020) - Kashat, Lawrence; Falcone, Todd; Carter, Bridgette; Parham, Kourosh; Kavanagh, Katherine R.
Resident wellness is increasingly recognized as critically important in otolaryngology education, and well-being education is now a requirement for all residencies. The objectives of this pilot study are to (1) perform a needs assessment to determine the wellness topics most important to the residents, (2) determine systemic barriers to wellness through a structured focus group, and (3) describe a new method to approach resident well-being. An anonymous survey needs assessment, adapted from a published wellness curriculum, was administered to otolaryngology residents. Residents underwent a structured, anonymous focus group applying Maslow's hierarchy of needs. The focus group highlighted resident priorities and defined an action plan for the program. This method allows for an individual and systems approach to resident wellness. Involving residents may increase engagement, and this approach can identify barriers to wellness and provide the groundwork for a formal resident wellness curriculum.